2004
DOI: 10.1037/0002-9432.74.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Consistency in Assessing Conduct Disorder: An Experiment on the Effect of Social Context.

Abstract: The major objective of the diagnostic criteria in the Diagnostic and Statistical Manual of Mental Disorders (see, e.g., the 4th ed., American Psychiatric Association, 1994) has been to achieve better diagnostic consistency. This has proved to be an elusive goal, because the diagnostic criteria and their rules for application can be ambiguous. This study mailed systematically varied case vignettes of conduct disorder to a nationally representative sample of 1,500 mental health clinicians in order to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…The findings are consistent with recent studies that indicate that diagnoses made without information regarding youths' social contexts have limited reliability and validity (Hsieh & Kirk, 2003;Kirk & Hsieh, 2004; also see Wakefield, Pottick, & Kirk, 2002). Diagnoses may be more valid if they include information such as that provided by dimensional behavioral instruments such as the CBCL and other dimensional behavior measures (RubioStipec, Walker, Murphy, & Fitzmaurice, 2002).…”
Section: Boys Girls Boys Girls Boys Girls Boys Girls Boys Girls Boys supporting
confidence: 89%
“…The findings are consistent with recent studies that indicate that diagnoses made without information regarding youths' social contexts have limited reliability and validity (Hsieh & Kirk, 2003;Kirk & Hsieh, 2004; also see Wakefield, Pottick, & Kirk, 2002). Diagnoses may be more valid if they include information such as that provided by dimensional behavioral instruments such as the CBCL and other dimensional behavior measures (RubioStipec, Walker, Murphy, & Fitzmaurice, 2002).…”
Section: Boys Girls Boys Girls Boys Girls Boys Girls Boys Girls Boys supporting
confidence: 89%
“…In conjunction with previous work examining the influence of explanatory life event context on assessments of conduct disorder and artificial disorders, [35][36][37][38]40,41 clinical psychologists are consistently influenced by explanatory context across disorders in assessment, even when the DSM is inconsistent in its treatment of explanatory context between disorders (e.g., between MDD and PTSD, in which a traumatic life event is one of the formal criteria for diagnosis 43 ). As argued in previous work, 57 although the DSM is often predominantly descriptive, clinical psychologists seem to push beyond the surface and incorporate causal factors into their assessments.…”
Section: Discussionmentioning
confidence: 94%
“…A classic textbook, The Selling of DSM (Kirk & Kutchins, 1992) directly challenged the DSM system as being more about social control than reliable or socially sensitive diagnoses. Kirk and Hsieh (2004) conducted a fascinating study that showed that case vignettes that met the conduct disorder criteria but added social context resulted in greater variability in diagnostic decisions by mental health clinicians. Kirk (2005) recently edited a thought-provoking textbook with various authors that confront the growing dependence on psychiatric medication to sedate rather than solve social issues, the flawed DSM system, and the covert subservient relationship that social work has to biological psychiatry.…”
Section: Introductionmentioning
confidence: 99%